Prostatitis and male infertility - Lin Hua; Xintao Gao; Junfeng Zhan; Xiaolong Wu; Hanchao Liu (The Aging Male)
Infertility is a pressing reproductive health issue in modern society, with male factors accounting for approximately 50% of all cases. However, most research on male infertility has primarily focused on the testis, often ignoring the critical role of the prostate. As the largest male reproductive gland, the prostate plays a vital role in semen quality. Prostatic fluid, a major component of semen, significantly influences sperm function and overall male fertility. Prostatitis, the most common prostate disorder among men, particularly with advancing age, can severely impair reproductive health. This article aims to explore the fundamental physiological functions of the prostate, the etiology of prostatitis, and its impact on sperm health. It also discusses potential treatment strategies for prostatitis. Through this review, we hope to deepen understanding of the prostate’s crucial role in male infertility.